Ibm Bagi Petambak Udang Tradisional di Desa Pangkah Wetan, Kecamatan Ujung Pangkah, Kabupaten Gresik, yang Mengalami Gagal Panen Secara Terus Menerus [ Ibm for Traditional Shrimp Farmers in Pangkah Wetan Village, Ujung Pangkah District, Gresik Region, That Fail Harvesting In Continuoesly] - Sudarno Sudarno; Gunanti Mahasri; Kismiyati Kismiyati (Faculty of Fisheries and Marine Universitas Airlangga, 2015)
Abstract Tiger shrimp (Penaeus monodon Fab) is one of the economically important shrimp, until 1992 became the most important of non petroleum export commodity from fishery sector. Since the end of 1993 up to now, the Penaeus monodon Fab death level has been relatively high and due to this circumstance have been caused many ponds collapsed so that the shrimp production was dramatically declined for year by year. Ujung Pangkah District is one of the Gresik Region areas which have big fisheries potensial, aspecially for the breakist water pond, that the topest as the other district. There are a lot of shrimp dead casis until now. But, so that 80% of breakist water pond were broken and not operational. The objective of this societies service activities is applicated a new shrimp culture technology with traditional plus probiocirculation system (PBS) for increases the shrimp harvest at Ujung Pangkah District Region of Gresik, from May until Oktober 2014. The method using in the activity were socialitation/counseling, dempond and guiding to application of the PBS model in one period. Monitoring and evaluation about this result were done in one month after the activity ending. This result showed that a positive indication. There was the knowledges of the farmer inceases by socialitation, it also applicated a model in the right method for shrimp culture. There were also showed that the PBS model can in ceased the shrimp harvest from 217 kg/ha to 872 kg/ha, it means was increased 303,7%. The conclution of this activity is the PBS model can used for breakist water pond idle revitalitation to increased the shrimp harvest and can applicates in more larges area in Gresik Region.